The first Brevinin-1 antimicrobial peptide with LPS-neutralizing and anti-inflammatory activities in vitro and in vivo - Tian, Maolin; Wang, Kai; Liang, Yan; Chai, Jinwei; Wu, Jiena; Zhang, Haiyun; Huang, Xiaowen; Chen, Xin; Xu, Xueqing (Frontiers in Microbiology, 2023)
Antimicrobial peptide is one important component of the first protective barrier of organisms. They not only have potent antimicrobial activity which can protect the body from the invading pathogens, but also participate in the immune regulation of the body. In this study, a Brevinin-1 peptide named by Brevinin-1GHd was identified from Hoplobatrachus rugulosus, and the similarity of mature peptide sequence among Brevinin-1GHd, Brevinin-1HL and Brevinin-1GHa supported the close species relationship between H. rugulosus, Hylarana latouchii and Hylarana guertheri. Moreover, the secondary structure of Brevinin-1GHd was found to possess α-helical characteristics and high thermal stability. In addition, Brevinin-1GHd could bind to LPS with a Kd value of 6.49 ± 5.40 mM and suppress the release of TNF-α, NO, IL-6 and IL-1β by inactivation of MAPK signaling pathway in RAW 264.7 cells induced by LPS. Furtherly, Brevinin-1GHd had a significant inhibitory effect on acute edema development in the right paw of mice injected by carrageenan. Thus, the significant LPS-neutralizing and anti-inflammatory activities of Brevinin-1GHd were demonstrated in this study, which made it become the first Brevinin-1 family peptide with anti-inflammatory activity reported so far, and the biological activity of Brevinin-1GHd made it promising to be a novel therapeutic drug for infectious inflammation.